La relatividad, lo verosimil y Ia toma de conciencia:Una problematizacion Comunitaria - Cronick, Karen (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This is a theoretical paper that has grown out of practical community facilitation. It is related to the process of "reflection" that follows community "action" in the Participative Action Research Model. I discuss the relationship between: a) relativism, considered as an ethical and cultural stance in community facilitation, and b) the practice of consciousness raising. I believe that there is a conceptual conflict between the goals of empowering community members and the doctrine of radical cultural relativism. I propose the adoption of a limited pragmatic tolerance instead of relativism for the field.